2011
DOI: 10.1016/j.jas.2010.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and origin of black and red Magdalenian pigments from Grottes de la Garenne (Vallée moyenne de la Creuse-France): a mineralogical and geochemical approach of the study of prehistorical paintings

Abstract: a b s t r a c tPigments sampled from wall paintings and from crayons taken on the floor, at the Grottes de la Garenne (Saint-Marcel e Indre, France) have been analyzed and characterized by infrared spectroscopy, Raman micro-spectroscopy, X-ray diffraction, ICP/MS and analytical TEM. The red pigment used for the wall paintings is mainly composed by hematite, clays, carbon matter and carbonates. Results on the red pigments show that the compositions of the paintings are similar to that of some crayons. Regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…A(a), is frequently observed in these specimens. A study on Magdalenian pigments from Grottes de la Garenne (France) assigned this band to cryptomelane, in disagreement with UV Raman data for this mineral . This band could also be assigned to todorokite, pyrochroite and manganosite .…”
Section: Resultsmentioning
confidence: 80%
“…A(a), is frequently observed in these specimens. A study on Magdalenian pigments from Grottes de la Garenne (France) assigned this band to cryptomelane, in disagreement with UV Raman data for this mineral . This band could also be assigned to todorokite, pyrochroite and manganosite .…”
Section: Resultsmentioning
confidence: 80%
“…Moreover, these compounds have been used in various applications, for example, in art works as pigments for pottery, mural paintings, and stained glass. Therefore, their proper characterization might provide an important tool in cultural heritage studies, or when addressing the degradation of art works due to the weathering …”
Section: Introductionmentioning
confidence: 99%
“…Darchuk et al found red and yellow ochres in rock‐painting pigments from Egypt (Gilf Kebia area), and claimed also the presence of rutile. Jezequel et al investigated, using Raman, X‐ray diffraction, ICP/MS and analytical TEM, some paintings from the Magdalenian age in the Grottes de la Garenne (Saint‐Marcel, Indre, France) and objects found on the floor, which could have been used as ‘crayons’. Hematite, clays, carbon matter and carbonates were found in the red pigments and in some crayons.…”
Section: Introductionmentioning
confidence: 99%